Expert opinion on the way forward for improving maternal influenza vaccination in India. (3rd July 2021) - Purandare, Chittaranjan N.; Preiss, Scott; Kolhapure, Shafi; Sathyanarayanan, Sripriya
ABSTRACT: Introduction: : Rates of maternal vaccination against influenza are extremely low in India. An expert panel of obstetric–gynecologists and pediatricians met to develop consensus-based recommendations for improving awareness of the benefits of influenza vaccination during pregnancy in India. Areas covered: : The group discussed experiences of influenza infection in pregnancy and infancy before focusing on maternal vaccination practices in India, including the degree of communication between obstetric–gynecologists and pediatricians and opinions on optimal timing for vaccination. The impact of inconsistent vaccine prescription practices by healthcare providers was discussed, as well as current clinical recommendations on maternal influenza vaccination. Expert opinion: : Although clinical evidence demonstrates the benefit of maternal influenza vaccination in any trimester, influenza vaccination is not widely accepted in India as an integral part of antenatal care. There is a lack of familiarity among obstetricians of clinical guidelines on maternal influenza vaccination. This can be addressed with an education campaign targeting obstetricians and other providers of maternal healthcare. With variable influenza seasons between regions in India, common vaccine stock shortages, and data suggesting influenza vaccination is feasible anytime in pregnancy, all opportunities to offer vaccination to this high-risk group for severe influenza disease should be considered.